2021
DOI: 10.2215/cjn.02390221
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Phenotype in Patients Undergoing Long-Term Hemodialysis Awaiting Kidney Transplantation

Abstract: Background and objectivesAge and comorbidity-related sarcopenia represent a main cause of muscle dysfunction in patients on long-term hemodialysis. However, recent findings suggest muscle abnormalities that are not associated with sarcopenia. The aim of this study was to isolate functional and cellular muscle abnormalities independently of other major confounding factors, including malnutrition, age, comorbidity, or sedentary lifestyle, which are common in patients on maintenance hemodialysis. To overcome thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The reduced energy production is accompanied by increased formation of reactive oxygen species, which has detrimental effects in muscle, leading to a vicious circle inhibiting bioenergetic processes and enhancing apoptotic processes. In line with the findings of Souweine et al (4), autophagy and mitophagy appear to be important features of uremic myopathy. Upregulation of proteins associated with autophagy has been found in animal experiments.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The reduced energy production is accompanied by increased formation of reactive oxygen species, which has detrimental effects in muscle, leading to a vicious circle inhibiting bioenergetic processes and enhancing apoptotic processes. In line with the findings of Souweine et al (4), autophagy and mitophagy appear to be important features of uremic myopathy. Upregulation of proteins associated with autophagy has been found in animal experiments.…”
supporting
confidence: 89%
“…In summary, the study by Souweine et al (4) reveals some specific features of muscle abnormalities in selected patients on long-term hemodialysis without apparent comorbid factors affecting muscle composition. In spite of maintained muscle mass and strength, the described phenotype with a relative reduction of oxidative type 1 fibers and loss of mitochondria explain at least in part the low endurance capacity encountered in this group.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…may affect muscle production in response to anabolic stimuli in the body 29 . One study reported cyclosporine reduced mitochondrial activity in skeletal muscle cells in mice 30 . In another study, it was concluded that tacrolimus causes deterioration in the regulation of skeletal muscle mass because of increasing energy use by accelerating the metabolism 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent cohort of fit subjects on maintenance dialysis awaiting kidney transplantation, skeletal muscle studies demonstrated preserved muscle fiber cross-sectional area, and no increase in sarcopenia, despite lower endurance capacity compared to controls. Fiber typing studies of vastus lateralis muscle in the same cohort demonstrated a lower percentage of MyHC type I fibers with higher percentage of other MyHC fibers, reflecting a switch from slow to fast fiber type [ 33 ]. On the other hand, in a similar study by Lewis et al [ 34 ], on vastus lateralis muscle biopsies of subjects on maintenance dialysis, there was a small but significant increase in type I fibers with a small decrease in IIx fibers.…”
Section: Discussionmentioning
confidence: 99%